Proposal for the design of a mechanism for the distribution of benefits derived from the utilisation of genetic resources and associated traditional knowledge - Vallejo Trujillo, Florelia (2020)
Achieving a distribution of benefits derived from the use of genetic resources (GR) and traditional knowledge (TK) has proven to be a target difficult to achieve. For this reason, the objective of this thesis is to find the key elements useful for a feasible implementation of ABS. Such elements respond to the problems evidenced throughout this work regarding the difficulties experienced so far in the operationalisation of ABS. Those problems are, (i) that developing proposals for the application of legal frameworks on this very specialised, complex, fragmented, and highly political issue, requires more than one approach, (ii) that the accessible proposals on how to address ABS are predominantly theoretical, and (iii) that there seems to be resistance to the inclusion of new aspects in the discussion on ABS. Therefore, the hypothesis of this thesis is that the experience gained by countries in the implementation of ABS laws provides practical ways to solve some of the issues related to the achievement of benefit-sharing that should be explored to complement the existing theoretical proposals. For that reason, the adoption of a practical rather than a theoretical approach has been preferred. However, solving those problems requires theoretical support. Thus, the analysis found in López, de Sousa Santos, and McCann and March have been acknowledged. From different perspectives, these authors support the creation of legal systems according to the way people behave in their daily life. Fundamental aspects taken into consideration in the current study include the variety of conceptual recommendations aimed to achieve ABS. Another aspect is the legal frameworks and mutually agreed terms (MATs) available in the ABS Clearing House (ABSCH) of the CBD. This work concludes that the most significant obstacles to effective implementation of ABS are: (i) the national/bilateral approach to the CBD; (ii) the lack of specific regulation for access to GR ex-situ in the CBD; and, (iii) the application of the concept of public domain in the ABS context. Due to the lack of agreement between the Parties concerned, these obstacles are not about to be amended soon, and, for now, possible solutions can only be sought through national laws. This thesis considers that benefit-sharing could be better addressed if provider countries were to abandon the current schema of entering into single negotiations every time a GR or a TK is accessed. This task, together with controlling and monitoring all the different ways these resources could be used once access is granted, seems so vast that it would be very difficult to accomplish. Instead, it is suggested that a mandatory sharing of non-monetary benefits with a voluntary sharing of monetary benefits is the best solution. The sharing of benefits could be encouraged by: (i) introducing a certificate of compliance upon actual sharing of non-monetary benefits; and (ii) providing tax benefits for the sharing of monetary benefits. The use of mutually agreed terms (MATs) is recommended as a tool to facilitate dispute resolution at an international level. Given the potential that the global multilateral benefit-sharing mechanism (GMBSM), proposed in Article 10 of the NP, has in achieving benefit-sharing, the implementation of a basic GMBSM is suggested. Modifications of this mechanism could be introduced by the Parties as they reach new agreements.